History Shock : When History Collides with Foreign Relations - Dickson, John S. (John Shields) (Book collections on Project MUSE., 2021)
"As John Dickson learned from his twenty-six-year career as an American diplomat, working in the Foreign Service teaches you as much about your own culture as it does about other cultures. We are accustomed to hearing about "culture shock"--that sense of disorientation and discomfort that comes from living in a place so unlike one's native environment. Dickson discovered something more profound than differences in cuisine and social customs. Over the course of his career, he experienced what he calls history shock: the sense of disorientation and discomfort that comes from seeing the present through a past differently constructed. His foreign counterparts were drawing on a history that he never learned and thus saw present-day events in completely different ways. That historical gap was as wide, if not wider, than any cultural gap, resulting in complex situations that could have been avoided or improved with a shared historical understanding. History Shock is both a memoir of Dickson's time in the Foreign Service and a lesson in historical forgetfulness. In recounting his experiences in places like Mexico, Canada, South Africa, Haiti, and Peru, Dickson helps bridge the historical gap between readers in the United States and residents of other nations who have never forgotten the traumas of the past. History Shock thus serves as a much-needed guide in crosscultural understanding at a time when there is so much misunderstanding"--